(untitled) (Journal of Partial Differential Equations, 2014)
We establish the global existence and uniqueness of classical solutions to the Cauchy problem for the two-dimensional isentropic compressible Navier-Stokes equations with smooth initial data under the assumption that the viscosity coefficient μ is large enough. Here we do not require that the initial data is small.